A post-Keynesian regulatory model of privatization - AlHussaini, Wissam (2009)
Many studies of privatization adopt the neo-liberal model which focuses on financial and economic distributional outcomes, and ignores social costs transferred to the state or broader society. We adopt a post-Keynesian point of view by identifying the social outcomes of privatization and the recipients of their effect in the society. We review regulation theory and discuss the effects of regulation on social and financial outcomes. Finally, we introduce a balanced regulatory model to show that privatization can become a process that achieves economic development and realizes broader social objectives.